Penyuluhan Edukasi Tentang Kesadaran Mahasiswa Dalam Beretika Prodi MIK STIKes Santa Elisabeth Medan - Pomarida Simbolon; Bernad Julvian Zebua; Ita Monita Munthe; Jetslin Simbolon; Lea Sri Ita; Scere Sophia Sitorus (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2024)
Awareness is a condition where a person understands the rights and obligations that he must carry out. Someone who is aware and understands will definitely carry out their responsibilities seriously (Muldiah, 2023). Studentship also comes from the sub-word student, while student is further divided into two syllables, namely maha and student. Maha means "ter" student means "student", so in the sense student means educated. This means that a student not only studies the field he is studying but also applies it and is able to innovate and be highly creative in that field (Muldiah, 2023). And ethics comes from the Greek word 'ethos' meaning custom. Ethics relates to values, good ways of living, good rules of life and all habits that are adhered to and passed down from one person to another or from one generation to another